Discussion of "Iterative Formulas and Estimation Formulas for Computing Normal Depth of Horseshoe Cross-Section Tunnel" by Jiliang Liu, Zhengzhong Wang, and Xing Fang - Gupta S.K.; Singh V.P.; Shukla S.K. (My University, 2025)
[No abstract available]